Assessment on the Use of Monitoring and Evaluation System in Constituency Development Fund, Nairobi County - Matetai, Monicah; Yugi, Philemon (Journal of Public Policy and Administration, 2016)
Purpose: The purpose of this study was to assess the use of monitoring and evaluation system for Constituency Development Fund, Nairobi County Methodology: The study used a descriptive survey research design. The unit of analysis was the Constituency Development Fund (CDF) in Nairobi County. The target population comprised of 187 committee members of the 17 constituencies. The sample size for this study was55 obtained using simple random sampling. The researcher used a questionnaire to obtain primary data. The questionnaires were self-administered. Quantitative data was analyzed using descriptive and inferential statistics and presented in percentages and frequencies. Qualitative data was analyzed using content analysis and presented in prose form. Both quantitative and qualitative data was compiled to generate the final project report. Results: Study findings indicated that there exists a functional monitoring and evaluation systems in the Constituency Development Fund in the County of Nairobi. Similarly, the study indicated that monitoring and evaluation influenced decision making in the Constituency Development Fund in the County of Nairobi. The study also indicated that there exist challenges affecting the effectiveness of monitoring and evaluation system for Constituency Development Fund in the County of Nairobi. Unique contribution to theory, practice and policy: The study recommends that funds work plan and costs should be set aside to enhance monitoring and evaluation activities in the Constituency Development Fund in the County of Nairobi. The study recommended that further research need to be conducted on the same topic but in another County so as to give comparisons to the current study. Similarly, a study can be undertaken to assess the existence of monitoring and evaluation activities in the Youth Development Fund, County Government projects, National Government projects and Self-help groups around the country.